Diseño mecatrónico y desarrollo de prototipo de máquina reprogramable y flexible para dibujo en 2D (2013)
In this paper is shown the development of a mechatronic design of a programmable, reprogrammable, flexible 2D-drawing prototype machine, as multidisciplinary project in Mechatronics Engineering. The project which includes modeling, simulation and technologies` and interfaces implementation, with synergistic integration of the three basic areas of Mechatronics: Mechanics, Electricity / Electronics and informatics. To achieve this goal the following tasks were done: mechanical system´s mathematical modeling, CAD, electronic control system´s modeling and simulation, servomechanism design, integration of systems and programming software design, and prototype testing and optimization. To develop the final prototype, four servomechanisms alternatives were analyzed and evaluated in order to find the best solution for the sought solution, such as: servo-pneumatic and electropneumatic servo and ball screw nut joint, servo-worm and helical wheel servo-pulley, and flexible transmission cable / pulley and belt.